2022
DOI: 10.1371/journal.pntd.0010388
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning-based in-hospital mortality prediction of HIV/AIDS patients with Talaromyces marneffei infection in Guangxi, China

Abstract: Objective Talaromycosis is a serious regional disease endemic in Southeast Asia. In China, Talaromyces marneffei (T. marneffei) infections is mainly concentrated in the southern region, especially in Guangxi, and cause considerable in-hospital mortality in HIV-infected individuals. Currently, the factors that influence in-hospital death of HIV/AIDS patients with T. marneffei infection are not completely clear. Existing machine learning techniques can be used to develop a predictive model to identify relevant p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…Multiple studies had demonstrated that respiratory failure, shock, high urea levels, and signi cantly lower PLT are predictive of poor outcomes and prognosis in HIV patients with talaromycosis. In deceased patients, AST/ALT rate was 3.07, which is signi cantly higher than that in survivors (1.96) [21]. Similar ndings were present in Histoplasma, with signi cantly higher AST/ALT than in other localized lung diseases.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Multiple studies had demonstrated that respiratory failure, shock, high urea levels, and signi cantly lower PLT are predictive of poor outcomes and prognosis in HIV patients with talaromycosis. In deceased patients, AST/ALT rate was 3.07, which is signi cantly higher than that in survivors (1.96) [21]. Similar ndings were present in Histoplasma, with signi cantly higher AST/ALT than in other localized lung diseases.…”
Section: Discussionsupporting
confidence: 66%
“…Six deceased patients (6/7) had signi cantly elevated CD4 + /CD8 + T cell ratios, 11 survivors (11/32) exhibited elevated CD4 + /CD8 + T cell ratios, and the rest (21/32)were reduced or normal. Therefore, immunological pro ling of talaromycosis patients should not be limited to CD4 + T cell counts but rather should comprehensively measure CD4 + T cells, CD8 + T cells, and the CD4 + /CD8 + ratio [16,21]. Follow up data for of AST, ALT, and other tests were lacking in IEI patients, and the relationship between IEI and hepatic injury in the context of talaromycosis needs to be further studied.…”
Section: Discussionmentioning
confidence: 99%
“…C-reactive protein is an acute protein mainly produced by hepatocytes that increase dramatically in response to injury, infection, and inflammation, which plasma level can reflect the severity of inflammation ( Sproston and Ashworth, 2018 ). Invasive T. marneffei infection can cause multiple organ damage and CRP is significantly increased in patients with poor prognosis ( Sun et al, 2021 ; Shi et al, 2022 ). Studies have shown that drug-metabolizing enzymes, including cytochrome P450 (CYP) isoenzymes, are decreased at the transcriptional levels during infection or inflammation, which leading to reduce the metabolism of VRC ( Renton, 2004 ; Aitken and Morgan, 2007 ; van Wanrooy et al, 2014 ; Encalada Ventura et al, 2015 ; Veringa et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…This pathogen grows in the filamentous form at 25°C and in the yeast form at 37°C. It is mainly prevalent in Southeast Asia and South China ( Ying et al., 2020 ; Sun et al., 2021 ; Li et al., 2022 ; Shi et al., 2022 ), with a mortality rate of up to one-third ( Narayanasamy et al., 2021 ). In recent years, along with an increase in the frequency of organ transplantation, T. marneffei infections have been increasingly reported, and the affected area has a tendency to expand ( He et al., 2021 ; Shen et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%